2012
DOI: 10.1007/s11302-012-9331-6
|View full text |Cite
|
Sign up to set email alerts
|

High glucose and free fatty acids induce beta cell apoptosis via autocrine effects of ADP acting on the P2Y13 receptor

Abstract: While high levels of glucose and saturated fatty acids are known to have detrimental effects on beta cell function and survival, the signalling pathways mediating these effects are not entirely known. In a previous study, we found that ADP regulates beta cell insulin secretion and beta cell apoptosis. Using MIN6c4 cells as a model system, we investigated if autocrine/paracrine mechanisms of ADP and purinergic receptors are involved in this process. High glucose (16.7 mmol/l) and palmitate (100 μmol/l) rapidly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…Therefore, low concentrations of ATP in the cell culture medium [9] could suffice to elevate intracellular calcium to a degree that activates ANO1. In addition, high glucose may also increase paracrine release of ATP that stimulates P2Y2R [24]. Furthermore, we have shown that high glucose leads to increased expression of P2Y2R in plMDCK cells which could render the cells more susceptible to extracellular ATP.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, low concentrations of ATP in the cell culture medium [9] could suffice to elevate intracellular calcium to a degree that activates ANO1. In addition, high glucose may also increase paracrine release of ATP that stimulates P2Y2R [24]. Furthermore, we have shown that high glucose leads to increased expression of P2Y2R in plMDCK cells which could render the cells more susceptible to extracellular ATP.…”
Section: Discussionmentioning
confidence: 82%
“…These data indicate that there is an association between DM and oxidative stress and that RSV is able to successfully attenuate these conditions. INS secretion from pancreatic islet β-cells is regulated by a number of factors; an increase in blood glucose is the predominant trigger; however, fatty and amino acids may also act as direct or indirect stimuli (31). It has been reported that PA induces lipotoxicity in rat INS-producing cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of the effects of n-3 can include a change in the composition of lipidic membranes, higher energetic expenditure, less formation of reactive oxygen species (ROS), and activation of peroxisome proliferator-activated receptor (PPAR), which act to decrease the activation of inflammatory pathways, such as c-Jun N terminal kinase (JNK) and nuclear factor-κB (NF-κB). Moreover, signaling modular molecules regulate the function of the immune system cells through liberation of cytokines, cell differentiation, and platelet aggregation [9,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%